22nd International Conference on Human-Computer Interaction With Mobile Devices and Services 2020
DOI: 10.1145/3379503.3403547
|View full text |Cite
|
Sign up to set email alerts
|

Save the Smombies: App-Assisted Street Crossing

Abstract: Using a smartphone while walking in urban traffic is dangerous. Pedestrians might become distracted and have to split their attention between traffic, walking and using the mobile device. The increasing level of automation in vehicles introduces novel challenges and opportunities for pedestrian-vehicle interaction, e.g external displays attached to automated vehicles. However, these approaches are hardly scalable and fail to provide clear information in a multiuser environment. We investigate whether a smartph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…While haptic feedback can avoid users constantly having to look at their phones while navigating through traffic situations, such implicit feedback is also limited in terms of its information capacity and might interfere with feedback from other apps (e.g., messenger apps). Holländer et al (2020a) evaluated on-screen guidance concepts for smartphone-assisted street crossing in front of automated vehicles, thus providing targeted communication cues to individual users. However, while information cues on hand-held devices could overcome the scalability problem of eHMIs, there are several limitations acknowledged by the authors.…”
Section: Hand-held Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…While haptic feedback can avoid users constantly having to look at their phones while navigating through traffic situations, such implicit feedback is also limited in terms of its information capacity and might interfere with feedback from other apps (e.g., messenger apps). Holländer et al (2020a) evaluated on-screen guidance concepts for smartphone-assisted street crossing in front of automated vehicles, thus providing targeted communication cues to individual users. However, while information cues on hand-held devices could overcome the scalability problem of eHMIs, there are several limitations acknowledged by the authors.…”
Section: Hand-held Devicesmentioning
confidence: 99%
“…However, while information cues on hand-held devices could overcome the scalability problem of eHMIs, there are several limitations acknowledged by the authors. On the other hand, SmartCurbs (as one HMI example) are integrated into the surrounding environment, do not require constant visual attention, and provide information at the periphery of attention such as enabling barrier-free and easy access, while also addressing ethical considerations such as avoiding the use of smartphones in potentially dangerous traffic situations (Holländer et al, 2020a).…”
Section: Hand-held Devicesmentioning
confidence: 99%
“…The interaction issues between AVs and pedestrians have attracted a lot of attention in HCI research. Past research has explored various design approaches to facilitate AV-pedestrian interaction, such as audio signals (engine sounds, bell rings, and soft alarm sounds) [72], Light Signals [16,17,30], Augmented Reality (AR) projection on the road [63], Mobile Applications and Connected Devices [36,69], Internet Vehicle-to-Everything (V2X) Technology [75], Interfaces on Street Infrastructure [45] and external Human-Machine interface (eHMI) [26,42]. Empirical research on the aforementioned methods indicates that these approaches have their respective advantages in terms of clarity, familiarity, and politeness, yet they still present challenges.…”
Section: Related Work 21 Autonomous Vehicles-pedestrian Interaction D...mentioning
confidence: 99%
“…Regarding clarity, the effectiveness of Audio Signals is limited in conveying risk levels [72]; Light Signals are also inefficient in ambiguous situations and busy scenarios [16,17,30]; Street Infrastructure Interfaces may cause visual confusion and fail to indicate multiple pedestrians' intents, affecting clarity [45]. Regarding familiarity, AR [63] offers novel interaction methods but its complexity can increase cognitive load, reducing familiarity; the effectiveness of Audio Signals in conveying risk levels varies across environments, limiting clarity; Mobile Apps and Connected Devices provide intuitive, personalized interactions for understanding AVs' intentions but their effectiveness is contingent on widespread adoption and user familiarity [36,69]; V2X Technology enhances safety through effective communication but faces challenges in network latency and reliability, reflecting limited user familiarity [75].…”
Section: Related Work 21 Autonomous Vehicles-pedestrian Interaction D...mentioning
confidence: 99%
“…Furthermore, Holländer et al (2020) showed that the use of smartphone apps that display traffic guidance information (e.g., showing a green or red light depending on whether it is safe to cross or not or a red or green border on the left or right side of the user’s smartphone screen according to the approach side of the coming vehicle, or otherwise showing the user’s position together with the location of nearby vehicles) coupled with vibrotactile signals, enhanced pedestrian participants’ willingness to cross in videos of traffic scenarios, when compared with no guidance ( Holländer et al, 2020 ). In the same vein, Cœugnet et al (2017) demonstrated that the use of a vibrotactile wristband that emitted a vibration when the forthcoming crossing was judged to be unsafe helped to decrease the percentage of pedestrian decisions that led to collisions with an approaching car in a virtual reality environment ( Cœugnet et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%